Hyperintense Putaminal Rim at 3T Reflects Fewer Ferritin Deposits in the Lateral Marginal Area of the Putamen - Fujii, S. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: The aim of this study was to clarify the cause of hyperintense putaminal rim (HPR) on the basis of 3T MR imaging–pathologic correlations. MATERIALS AND METHODS: We evaluated brain MR images from 75 subjects 13 to 85 years of age on T2-weighted fast spin-echo (FSE) images at 3T. We also assessed HPR on postmortem T2-weighted FSE images from 4 postmortem cases 1, 12, 63, and 83 years of age. To clarify the cause of HPR, we used 3 staining methods: the Klüver-Barrera method to observe the myelin sheath, the Berlin blue method to observe hemosiderin, and ferritin immunohistochemistry to observe ferritin. The postmortem MR images were compared with the histologic findings in each case. RESULTS: HPR was absent or vague in subjects under 30 years of age but present in subjects in their 30s–60s and again became vague in those subjects older than 70 years of age. The postmortem MR imaging–pathologic correlations revealed that ferritin deposits were slight in the lateral marginal area of the putamen in the 63-year-old subject showing present HPR, but in the 83-year-old subject with no HPR, ferritin deposits were prominent in the lateral marginal area of the putamen as well as in other areas. CONCLUSION: Age-related disproportion in ferritin deposits between the lateral marginal area and the remainder of the putamen causes hypointensity of the latter and the relative hyperintensity of the former, which is depicted as HPR with 3T MR imaging.